3(x – 1) + 4( 2x – 3) = - 4



Odpowiedź :

Odpowiedź:

[tex]\huge\boxed{x=1}[/tex]

Rozwiązanie:

[tex]3(x- 1) + 4( 2x - 3) = - 4\\3x-3+8x-12 = -4\\11x-15 = -4 \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ / +15\\11x = 11 \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ / :11\\x = 1[/tex]

Odpowiedź:

3 ( x -1) + 4 ( 2x-3) = - 4

  3x - 3 +8x -12 = - 4

     11x= -4 +3 +12

     11 x= 11  /:11

          x=1

spr...  3*1 -3 + 8*1 -12 = - 4

           8-12= - 4

              -4= - 4

            L=P

Szczegółowe wyjaśnienie: